Extraction of American ginseng polysaccharide by ultrasound-assisted deep eutectic solvents-based three-phase partitioning: Process optimization, structural characterization, and anti-ulcerative colitis study - Zhongnan Wu; Chong Li; Junhao Li; Tanggan Wang; Meifeng Li; Leyi Zhao; Huimei Ye; Jiaheng Chen; Jiajia Zan; Lijun Song; Qian Zhang; Shaojie Zhang (Ultrasonics Sonochemistry)
Three-phase partitioning (TPP) is promising for isolating bioactive polysaccharides, but t-butanol’s environmental impact limits its application. Deep eutectic solvents can serve as a green and recyclable alternative to t-butanol. This study introduces an ultrasonic-assisted DES three-phase partitioning (UA-TPP-DES) system to extract and purify American ginseng polysaccharides (AGPs). The optimized DES-4, composed of lauric acid and nonanoic acid (molar ratio = 1:1), achieved a 35.28 % extraction yield under specific conditions and can be recycled five times with minimal yield loss. AGP-DES-4 has a broad molecular weight distribution (2.48–174.64 kDa) and mainly consists of mannose, glucose, galactose, and arabinose. In vivo Drosophila models show that AGP-DES-4 improves UC fly survival and enhances intestinal barrier function by regulating the proliferation and differentiation of intestinal epithelial cells (IECs) and intestinal stem cells (ISCs). Our results highlight the effectiveness of the AGP-DES-4 extraction method and its potential therapeutic value for treating UC.